2010
DOI: 10.2488/jwrs.56.41
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Wood Decay on the Shear Performance of Nailed Timber Joint

Abstract: Degradation of shear resistance of nailed joints by wood decay was estimated experimentally. We conducted decay treatments of Todomatsu Abies Sachalinensis specimen for compressive and single-shear tests of nailed joints with Todomatsu main members, steel side plates and CN50 nails by brown-rot fungus Fomitopsis palustris , which is commonly observed in Japan. After the decay treatment, we measured the compressive strength parallel to the grain and the single shear resistance of nailed joints, and the depth of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 10 publications
0
10
0
Order By: Relevance
“…We measured the depth of pin penetration for all specimens using Pilodyn, which is a widely used apparatus to measure degree of decay [4,6,8,10,17,18]. Pilodyn that we used has 2.5 mm pin diameter, 40 mm maximum penetration depth, and 6 J penetration energy.…”
Section: Depth Of Pin Penetrationmentioning
confidence: 99%
See 1 more Smart Citation
“…We measured the depth of pin penetration for all specimens using Pilodyn, which is a widely used apparatus to measure degree of decay [4,6,8,10,17,18]. Pilodyn that we used has 2.5 mm pin diameter, 40 mm maximum penetration depth, and 6 J penetration energy.…”
Section: Depth Of Pin Penetrationmentioning
confidence: 99%
“…A number of studies have investigated the strength of wood when exposed to wood-decaying fungi [1][2][3][4]. Recent studies have examined the effects of decay on the strength of timber joints with respect to the shear performance of nailed joints, dowel-type joints, and screwed joints exposed to decay fungi [5][6][7][8][9][10]. However, there has been little investigation into the relationship between the withdrawal strength of nails and decay.…”
Section: Introductionmentioning
confidence: 99%
“…There have been several researches on the strengths of nailed connections exposed to a wood-decaying fungus. Studies on nailed connections have been conducted with side members composed of oriented strand board [9,10], steel plate [11,12], plywood, and medium density fiberboard [13]. These studies have indicated the decrease in strength of nailed connections caused by the decay.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies that are based on the biological, biochemical and mechanical viewpoints [3][4][5][6][7][8][9][10][11] have been performed on the wood deterioration by brown-rot fungus.…”
Section: Introductionmentioning
confidence: 99%
“…Especially, because the strength deterioration of decayed wood may largely affect safety of timber structures, estimation of degree of deterioration have been performed on partially decayed wood. Methods applied in such studies to date are the pin-penetration depth [5,6], acoustic emission [7,8], infrared spectra [9,10], X-ray microdensitometry [11]. However, the values obtained by those were influenced by moisture content and distribution of decay.…”
Section: Introductionmentioning
confidence: 99%